Lateralization Effects on Cerebral Blood Flow in Patients With Unilateral Pulsatile Tinnitus Measured With Arterial Spin Labeling - Li, Xiaoshuai; Zhao, Pengfei; Qiu, Xiaoyu; Ding, Heyu; Lv, Han; Yang, Zhenghan; Gong, Shusheng; Wang, Zhenchang (Frontiers in Human Neuroscience, 2020)
Purpose: The aim of this study was to detect cerebral blood flow (CBF) differences in patients with left- and right-sided pulsatile tinnitus (LPT and RPT) and healthy controls (HCs) to further explore the lateralization effects of PT using arterial spin labeling (ASL). Methods: ASL data from 21 RPT patients, 17 LPT patients and 21 HCs were reviewed. Voxel-wise analysis and region of interest (ROI) analysis were performed to explore differences in CBF among the three groups. Tinnitus Handicap Inventory (THI) score and tinnitus duration were obtained from each patient. Results: Voxel-wise analysis showed that the CBF of the left inferior parietal gyrus was increased in both RPT and LPT patients compared with HCs (P < 0.001). ROI analysis revealed that the CBF of the left primary auditory cortex (PAC) was higher than that of the right, while the CBF of the right secondary auditory cortex (SAC) and auditory association cortex was higher than that of the left. These lateralization effects were present in all three groups. Compared with HCs, RPT patients exhibited increased CBF in the left PAC and SAC (PAC: P = 0.036; SAC: P = 0.012). No significant correlations were found between PT duration or THI score and altered CBF in above regions. Conclusion: Increased CBF in the left inferior parietal gyrus is a common feature in both RPT and LPT patients, regardless of the perceived side of PT. The lateralization effects of auditory cortices may be a physiological characteristic of the normal brain. These findings may provide a new perspective for understanding the neurological pathophysiology of PT.